A Worldwide Bibliometric Analysis of Tetrandrine Research in Recent Two Decades - Yang, Guang; Xie, Wenqing; Ding, Yilan; Wang, Weiyang; Huang, Cheng; Zhao, Tingxiao; Li, Yusheng (Frontiers in Pharmacology, 2022)
Background: Tetrandrine has been the focus of many studies in recent years. Currently, no bibliometric study in this field has been published. This study presents a bibliometric analysis of the articles on tetrandrine research from the WOS core database during the recent two decades. Methods: Documents were retrieved for further bibliometric analysis based on the search terms: (TI= (Tetrandrine OR Sinomeninea OR Hanfangchin A) AND PY= (2000-2021)). We used Microsoft Excel to conduct the frequency analysis, VOSviewer for data visualization, and RStudio for citation metrics and analysis. The standard bibliometric indicators such as the growth of publications, prolific authors, co-authorship, country contribution, preferred journals, top-cited articles and important institutions were applied in this study. Results: 490 documents were retrieved from WOS core database, the retrieved document type consists of 8 categories: 425 articles, 42 meeting abstracts, 8 reviews, 7 corrections, 3 editorial material, 2 proceedings paper, 1 letter, 1 retraction. Corrections and Retractions was excluded from this investigation. The left 482 document were included for furter bibliometric analysis. Conclusion: Based on our findings, there was a continuous growth of publications on tetrandrine research for 22 years since 2000. China was the largest contributor to tetrandrine research, followed by the United States. The most productive author was Cheng Y (Natl Taiwan Univ Hosp). The Acta Pharmacol Sin remained the main publication related to tetrandrine research. The Chinese Med Univ, is expected to be a good collaborating center in tetrandrine research. The use of tetrandrine in cancer treatment, could be the promising research subject areas to follow.